Online Pathology Education for Medical Students: Lessons Learned During Lockdown in Central Thailand - Laohawetwanit, Thiyaphat (Asian Medical Journal and Alternative Medicine, 2022)
This study aims to demonstrate a use case of asynchronous and synchronous online learning in pathology for medical students during the Novel Coronavirus 2019 (COVID-19) pandemic. Students’performances and preferences were satisfactory. Online learning should be included as a part of the pathology curriculum after the COVID-19 outbreak.